PENGARUH KEMAMPUAN KERJA, PERSEPSI PERAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI ADMINISTRASI UNIVERSITAS NEGERI JAKARTA - BETTY ZELDA SIAHAAN (Jurnal Manajemen Pendidikan, 2011)
The objective of this research is to find out the effects of the work ability, perceptions on role, and work motivation of the employees performance at the State University of Jakarta, conducted in 2009. The method used was a correlation study by survey. The sample size was 60 employees, selected at random. The data were analyzed by path analysis after placed in correlation matrix. The results showed as the followings, (1) the work ability and the role the perception have direct effects on work motivation; (2) the work ability and the role perception have direct effects on the employees performance; (3) the work motivation has also a direct effect on performance; (4) the work ability and role the perception have indirect effects on performance through work motivation. The implication of these results is that in the effort to improve the employee performance, the work ability, role perception and the work motivation should be considered.